2014
DOI: 10.1158/1535-7163.mct-14-0135
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the miR200 Family of microRNAs in Mesothelial Cells Suppresses the Dissemination of Ovarian Cancer Cells

Abstract: The TGFb-mediated alteration of the tumor microenvironment plays a crucial role in tumor progression. Mesothelial cells are the primary components of the tumor microenvironment for ovarian cancer cells; however, the exact role of TGFb-stimulated mesothelial cells in ovarian cancer progression remains uncertain. In this report, we examined the effects of TGFb-treated mesothelial cells on ovarian cancer progression. We show that TGFb-stimulated human primary mesothelial cells (HPMC) are able to promote cancer ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Furthermore, the surface of the peritoneum is histologically covered by a single layer of mesothelial cells (MCs), which may have a key function in the development of the tumor microenvironment that supports peritoneal metastasis of OvCa. Moreover, recent studies have shown that activated MCs play an important role in the development of peritoneal metastasis; these studies further demonstrated that MCs increase the adhesive and proliferative properties of OvCa cells. In fact, mesenchymal transition of MCs was reported to be induced by a variety of soluble factors in malignant ascites, and modification of extracellular matrix (ECM) on the mesothelial cells also promoted peritoneal metastasis of OvCa .…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, the surface of the peritoneum is histologically covered by a single layer of mesothelial cells (MCs), which may have a key function in the development of the tumor microenvironment that supports peritoneal metastasis of OvCa. Moreover, recent studies have shown that activated MCs play an important role in the development of peritoneal metastasis; these studies further demonstrated that MCs increase the adhesive and proliferative properties of OvCa cells. In fact, mesenchymal transition of MCs was reported to be induced by a variety of soluble factors in malignant ascites, and modification of extracellular matrix (ECM) on the mesothelial cells also promoted peritoneal metastasis of OvCa .…”
Section: Introductionmentioning
confidence: 74%
“…This study was approved by the institutional ethics committee of Nagoya University (approval number: 1234). Stable cell lines that expressed ZsGreen or luciferase were generated using a recombinant retrovirus following a previously described method 51 . In brief, 293 T cells were transfected with the pQCXIP vector encoding each gene as well as with the pVPack-GP and pVPack-Ampho vectors for the production of retrovirus particles (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was shown that TGF β -stimulated human primary mesothelial cells, which induced expression of MMP-2 and MMP-9, were able to promote cancer cell attachment and proliferation through downregulating members of the miR-200 family. Consequently, the delivery of miR-200 family miRNAs to mesothelial cells in mice inhibited ovarian cancer cell implantation and dissemination 56 . We recently showed that the direct interaction of OvCa cells with mesothelial cells, which cover the surface of the omentum, causes a DNA methyltransferase 1 (DNMT1) mediated decrease in the expression of miR-193b in the cancer cells 57 .…”
Section: Introductionmentioning
confidence: 99%